STUDI STRATEGI PROMOSI USAHA SALON KECANTIKAN DI KOTA PADANG - Cikyah, Cikyah; Rahmiati, Rahmiati; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to describe the promotion strategy of beauty salon business basedon promotion scope of advertising, personal selling, sales promotion, publicrelations, and word of mouth, At the beauty salon business in Padang city of WestSumatra. The research approach is Quantitative Descriptive. The population is allbusiness leaders from 20 beauty salons in Padang City, amounting to 20 peoples.Data were taken using Likert scale questionnaire, data analysis using techniquepercentage level achievement of respondent. The results showed that (1) Theaverage percentage of advertising indicators 60,75% with bad category. (2)Average percentage of personal selling indicator 69% with medium category. (3)The average percentage of sales promotion indicator is 68,37% is moderatecategory. (4) Indicators of public relations have an average score of 64,1% withbad category. (5) The percentage of mouth to mouth indicator is 79,71% withgood category. Based on the results of research, it is suggested that beauty salonbusiness to further improve in implementing sand implementing a promotionalstrategy consisting of 5 such indicators for business success can be achieved.Kata kunci: Strategi promosi, Usaha salon kecantikan